‘State Feminism' dan perjuangan wanita di Tunisia pasca Arab Spring 2011 - Mohd Irwan Syazli Saidin; Nur Amira Alfitri (Penerbit Universiti Kebangsaan Malaysia, 2020)
Over the last decade, the Arab Spring phenomenon in the Middle East and North Africa has brought significant transformation towards Tunisia’s political landscape. During the 14 days of street protest, Tunisian women have played critical roles in assisting their male counterparts in securing the ultime goal of the revolution – regime change. This article argues that after the 2011 revolution, the new Tunisian government has gradually adopted the principal idea of state feminism, which emphasizes on the role of ruling government via affirmative action in supporting the agenda of women’s rights. In so doing, this article examines the connection between state feminism and the plight of women’s struggles in Tunisia after the 2011 revolution and, looks into the impact of top down polices, and government approaches towards improving the status of women. This article concludes that women in the post revolutionary era have experienced a new trajectory in political and social freedom,the country has recorded a spike increase in the number of active female lawmakers, government executives, politicians, electoral candidates and the emergence of human right groups, gender activists and feminist movements. All these ‘women’s actors’ have directly involved in the process of drafting the new Tunisian constitution, which resulted in the acknowlegdement of women’s rights protection via article 46 in 2014 and the Nobel Peace Price Award in 2015.